Sedentariness and Health: Is Sedentary Behavior More Than Just Physical Inactivity? - Panahi, Shirin; Tremblay, Angelo (Frontiers in Public Health, 2018)
Sedentary behaviour refers to certain activities in a reclining, seated or lying position requiring very low energy expenditure. It has been suggested to be distinct from physical inactivity and an independent predictor of metabolic risk even if an individual meets current physical activity guidelines. Over the past decades, a shift in the activity profile of individuals has been observed with vigorous physical activity and sleep being partly replaced by cognitive work, a potential neurogenic stress component considering its hormonal and neurophysiological effects, leading to various impacts on health. Mental work, for instance, may significantly increase glycemic instability leading to an increase in the desire to eat and thus, higher energy intakes. Furthermore, screen-based leisure activities (e.g. television watching) and screen-based work activities (e.g. computer use for work purposes) have often been considered together while they may not trigger the same stress response and/or use of substrate. Thus, the problems of sedentariness may not only be attributed to a lack of movement, but also to the stimulation provided by replacing activities. The objective of this review is to discuss the 1) recent evidence and current state of knowledge regarding the health impact of sedentary behaviours on health; 2) potential neurogenic effects of cognitive work as a sedentary behaviour; 3) link between sedentary behaviours and the diet; 4) resemblance between sedentary behaviours and the inadequate sleeper; and 5) potential solutions to reduce sedentary behaviours and increase physical activity.